Tribal Forest Certification: An Assessment of Policy Impacts of Forest Certification Opportunities for Indian Tribes - Caldwell, Christopher Michael (My University, 2014)
The concept of forest certification has grown over the past two decades as a proposed solution, beyond traditional governmental authority, to address long standing issues with forest resources, particularly aimed at the southern hemisphere. The growth of forest certification as a tool to promote sustainable forest management has also generated a growing body of literature grounded in areas of economics, social sciences, politics, and ecology. One particular area has been forest certification?s derivation of authority based on markets and not traditional means of governmental authority. This is interesting when examined within the context of the unique legal and historical governance structure and relationships associated with Indian tribes and the management of their resources. The primary question examined was whether non-state (that is, non-governmental) market- driven governance systems might impact management of Indian tribes? forest resources, and in what ways? This research developed an Indian Country case study for an environmental policy analysis of possible impacts for a proposed tribally developed certification program. Based on this research, the very nature of forest certification and its ability to generate support for its legitimacy as a tool to promote sustainable forestry continues to hang in flux, thereby negating some of its perceived impacts to tribal governmental responsibilities. However, lessons derived from a comparison of existing cases studies indicate pro-active measures positioned some to better counteract what were perceived as outside influences impacting decision-making authority. In addition, the comparison of the Indian Country case study with other case studies provides a general framework that could help future research efforts for Indian Country and individual Indian tribes as they further consider forest certification and its policy impacts.
"A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Environmental Science and Policy." University of Wisconsin--Green Bay. Dissertations. Includes bibliography. Approved: Dr. Michael Kraft, major professor; Dr. John Stoll, major professor; and Dr. Gregory J. Davis, director of graduate studies; thesis committee members: Dr. David Helpap, Dr. Elizabeth Wheat. LC classification: SD387.E58. Print version: OCLC#889083814.
Keywords: Indian tribes; Forests and forestry--Certification--United States.; Sustainable forestry--United States.; Forest management--United States.; policy; Indian country (United States law)--Economic aspects.; Indians of North America--Industries.; assessment; certification; tribal forests